THE EFFECT OF AUDIT RISK ON AUDIT QUALITY THROUGH AUDIT FEES AT KAP IN WEST JAKARTA - Jatmika, Dodik; Nurdin, Muhammad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze (1) the effect of audit risk on audit fees in West Jakarta, (2) the effect of audit risk on audit quality in West Jakarta, (3) the effect of audit fees on audit quality in West Jakarta, and (4) the effect of audit risk on audit quality through audit fees in West Jakarta. This study used a population of Public Accounting Firms (KAP) located in West Jakarta, totaling 107 KAP, with sampling based on the survey method. The results showed that: (1) audit risk has a positive effect on audit fees, (2) audit risk has a negative effect on audit quality, (3) audit fees have a positive effect on audit quality, and (4) audit risk affects audit quality through audit fees in West Jakarta KAP.Â Keywords: Audit Risk, Audit Fee, Audit Quality, Public Accounting Firm, West Jakarta.Â Â